A THIRD USE VALUE OF ACCOUNTING. - Littleton, A. C. (The Accounting Review, 1950)
Abstract The study of accountancy may be said to possess three primary use values: (1) as a foundation for a professional career in public accounting, (2) as providing knowledge of an information service for business management and investors, (3) as one way of leaning disciplined thinking about dealing with data. The first two uses are well known and need no elaboration here. The third use value is the sort usually attributed to mathematics and statistics. But accounting also insists on accurate identification of detail and the organization of data in a meaningful way. Its study at the university level provides some of the same kind of beneficial discipline as these other subjects, and therefore it possesses general educational values in addition to the more strictly technical values for students of business management and professional accounting. Use values such as these have been clearly recognized as lying in the study of accounting. Because of this, there has been a widespread acceptance of the subject matter as useful outside of a purely occupational framework for a career in accounting as such.